Distance Learning Solutions During the Covid 19 Pandemic At Aceh Tamiang Islamic High School - Muhammad Jailani; Alfiana Utama (CV. Pusdikra Mitra Jaya, 2022)
Distance learning is a solution during the COVID-19 pandemic to overcome the anxiety of teaching and learning activities that do not return as usual. This study provides a description of how distance learning is implemented, the obstacles faced and the solutions that are tried to be offered to distance learning implementers. This research was conducted using a qualitative approach, The data collection technique is triangulation (observation, interview and documentation study). The results of the study indicate that learning by using the Zoom, WhatsApp, Google Meet and Google Classroom applications has not been able to guarantee effectiveness in distance learning. Constraints experienced such as the internet network, less interesting learning materials, and boredom. The solution that is trying to be offered is by conducting digital innovation based on e-learning. Updating using e-learning, so that learning can be controlled, supervised by the campus. Activities that are e-learning can also provide new innovations for the world of digital-based education. So that proficiency in technology for databases can be implemented.